2011
DOI: 10.3233/jad-2010-101350
|View full text |Cite
|
Sign up to set email alerts
|

Proteome-Based Plasma Markers of Brain Amyloid-β Deposition in Non-Demented Older Individuals

Abstract: Blood-based markers reflecting core pathological features of Alzheimer’s disease (AD) in pre-symptomatic individuals are likely to accelerate the development of disease-modifying treatments. Our aim was to discover plasma proteins associated with brain amyloid-beta (Aβ) burden in non-demented older individuals. We performed discovery-phase experiments using two dimensional gel electrophoresis (2DGE) and mass spectrometry-based proteomic analysis of plasma in combination with 11C-PiB PET imaging of the brain in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
67
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 53 publications
12
67
3
Order By: Relevance
“…All five of these proteins have been previously identified in plasma as candidate biomarkers associated with AD disease status and/or pathology [4, 9, 2227]. In fact α2M and C3 are two of the most reproducible plasma protein markers of AD, associating with AD-related phenotypes in five independent cohorts [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All five of these proteins have been previously identified in plasma as candidate biomarkers associated with AD disease status and/or pathology [4, 9, 2227]. In fact α2M and C3 are two of the most reproducible plasma protein markers of AD, associating with AD-related phenotypes in five independent cohorts [5].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore a peripheral measure may also be a valuable biomarker in the preclinical stages. In 2013, for example, we reported a protein signature in nondemented elderly people from the Baltimore Longitudinal Study of Ageing (BLSA) that could differentiate between individuals who would go on to show amyloid pathology using PET imaging ten years later [9]. In the present study, we aimed to expand upon this work by increasing the coverage of the proteome investigated and by identifying proteins that are stable in their ability across time to reflect amyloid as a continuous measure in cognitively healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…There have been previous attempts to use arrays of peripheral biomarkers, with mixed results. [28][29][30][31][32] For example, the initial promising results of an 18-analyte signature developed on 83 patients 33 did not show good diagnostic accuracy on a subsequent separate set of subjects. 30 Most of the previous studies of arrays of plasma markers were either too small to detect differences or did not use powerful enough computational approaches to detect differences in the populations of proteins.…”
mentioning
confidence: 93%
“…Three studies have examined the relationship of plasma ApoE levels and positron emission tomography (PET) imaging of Aβ deposits using Pittsburgh Compound B (PiB) [7,16,17]. Analyses of data collected in the Alzheimer’s Disease Neuroimaging Initiative (ADNI) and the Australian Imaging, Biomarkers, and Lifestyle (AIBL) studies found that lower plasma ApoE levels correlated with increased global cortical PiB retention on PET imaging [7,16].…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of data collected in the Alzheimer’s Disease Neuroimaging Initiative (ADNI) and the Australian Imaging, Biomarkers, and Lifestyle (AIBL) studies found that lower plasma ApoE levels correlated with increased global cortical PiB retention on PET imaging [7,16]. However, in a smaller cohort of non-demented individuals enrolled in the Baltimore Longitudinal Study of Aging (BLSA), higher plasma ApoE levels correlated with increased PiB retention in medial temporal lobe regions [17]. …”
Section: Introductionmentioning
confidence: 99%